PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN MODAL KERJA TERHADAP RENTABILITAS PADA PT PELAYARAN SINAR MANDIRI SEJAHTERA KOTA BATAM - Dian Efriyenti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This study aims to determine whether the effect of cash turnover, turnover of receivables and working capital turnover affect the profitability on a cruise PT Sinar Mandiri Sejahtera Batam. Results from the study showed that the velocity of cash (X1) but not significant effect on return on equity with significant value 0,714> 0,05, receivables turnover (X2) effect on return on equity with significant value 0,010 <0,05, working capital turnover (X3) but no significant effect on return on equity with significant value 0,653> 0,05. Cash turnover, turnover of receivables and working capital turnover significant effect simultaneously (together) to variable return on equity. The test results demonstrate the value of 15,360 F count> F table 2,77 with a significance value of 0.000. Judging from the significant value that is less than 0,05 means the (H4) is accepted. Keywords: Turnover Cash, Accounts Receivable Turnover, Turnover Of Working Capital, Profitability.